Perceived leadership styles and teacher participation in decision-making process in selected family-owned schools in San Pedro, Laguna - Tancinco, Macrino Jesus R. (Animo Repository, 2002)
This study determines the leadership styles of administrators in the selected family-owned schools in San Pedro, Laguna, the extent of actual and desired teacher participation in decision making in the said schools, the correlation between this leadership style and the extent of participation of teachers in decision making, and the correlation between the teachers' demographic variables and the actual extent of their involvement in decision making. It also investigates the difference between the teachers' and administrators' perceptions on the actual and desired extent of teacher participation of decision-making processes. The study employed the descriptive and correlational methods of research. The instruments used were the Personal Profile questionnaire, the Teachers' Participation in School Decision-Making Process questionnaire and the Profile of Organizational Characteristics (POC) questionnaire. The study revealed that the leadership style of the administrators is benevolent-authoritarian. While teacher participation in decision-making in these schools is, at present, considerable, both administrators and teachers desired for more involvement of teachers in the said process. The administrators and teachers do not differ in their perceptions of the actual and desired extent of teacher participation in decision-making. The leadership styles of school administrators, and, almost all the demographic variables of teachers are not related to the extent of teacher participation in decision-making. Educational attainment of teachers is correlated to the extent of actual teacher participation of decision-making in the areas of student personnel services, faculty affairs, curriculum and instruction, and, finance and management. The difference between the actual and desired extent of teacher participation is highly significant, as perceived by both administrators and teachers. The research concludes that administrators of the selected family owned schools are benevolent authoritarian. Teachers participate considerably in the decision-making processes in these schools. The extent of teacher participation in decision-making is not related to the leadership styles of school administrators. The higher the educational attainment of teachers, the higher their involvement in decision-making. The administrators and teachers want more teacher participation in decision-making than the present extent of participation in all areas of school management. The investigation recommends that the study be made on the ways, techniques and models on how teachers could participate in decision-making in schools. It also recommends that a faculty program be developed in these schools whereby teachers will acquire the necessary academic, technical and procedural skills, as well as, the attitudes of willingness and concern needed to participate in the decision-making processes.